(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research aimed to study the obstacles of applying of E-tourism in the Syrian environment in terms of infrastructure, systems, laws and culture. Where a questionnaire was distributed to a sample of workers in tourist establishments with 294 workers. The study used the SPSS program for Statistical analysis of the data. The research found obstacles of applying of E-tourism in Syria. The most important of these obstacles are the lack of suitable infrastructure for network and internet, and the lack of Laws and Regulations of E-tourism, In addition to the lack of culture of the electronic environment in the Syrian tourism organizations. هدف البحث إلى دراسة معوقات تطبيق السياحة الإلكترونية في البيئة السورية من حيث البنية التحتية والأنظمة والقوانين والثقافة. حيث تم توزيع استبانة على عينة من العاملين في المؤسسات السياحية بلغت 294 عاملاً. وقد تم التحليل الإحصائي للبيانات باستخدام برنامج SPSS.وتمثلت نتائج البحث في وجود معوقات أمام تطبيق السياحة الإلكترونية في الجمهورية العربية السورية, وتتجسد أهم هذه المعوقات في عدم توفر بنية تحتية ملائمة لشبكة الاتصال والإنترنت، وعدم وجود أنظمة وقوانين تنظم السياحة الإلكترونية، بالإضافة إلى عدم وجود ثقافة التوجه نحو البيئة الإلكترونية لدى المنظمات السياحية السورية.